2001
DOI: 10.1046/j.1440-6047.2001.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

DietaryD‐psicose, a C‐3 epimer ofD‐fructose, suppresses the activity of hepatic lipogenic enzymes in rats

Abstract: D-Psicose (D-ribo-2-hexulose), a C-3 epimer of D-fructose, is present in small quantities in commercial carbohydrate complexes or agricultural products. Wistar male rats were fed experimental diets which consisted of 5% D-psicose, cellulose, D-fructose or D-glucose for 28 days. Abdominal adipose tissue weight was significantly lower (P < 0.05) in rats fed the D-psicose diet than in rats fed a D-fructose and D-glucose diets, even though the four dietary groups were offered the same amount throughout the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
99
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 28 publications
9
99
0
Order By: Relevance
“…We also showed that RSS reduced abdominal fat accumulation and serum glucose, insulin, and leptin levels in rats compared to HFCS (18). In our previous study, d-allulose suppressed lipogenic enzymatic activities in the liver compared to glucose or fructose in rats (19,20). Thus, RSS containing d-allulose seem to be effective in preventing body fat accumulation and obesity partly via lowered lipogenic enzymatic activities.…”
supporting
confidence: 54%
“…We also showed that RSS reduced abdominal fat accumulation and serum glucose, insulin, and leptin levels in rats compared to HFCS (18). In our previous study, d-allulose suppressed lipogenic enzymatic activities in the liver compared to glucose or fructose in rats (19,20). Thus, RSS containing d-allulose seem to be effective in preventing body fat accumulation and obesity partly via lowered lipogenic enzymatic activities.…”
supporting
confidence: 54%
“…Since serum adipocytokines are secreted from adipose tissues, it is pertinent that D-psicose influenced neither adipose tissue weights nor serum levels of adipocytokines. We previously demonstrated that D-psicose provides no energy in rats (3), and that intra-abdominal adipose tissue weight was not different between the diets with 5% D-psicose and cellulose after 28 days (17). Moreover, we previously reported that 5% D-psicose supplementation did not alter gene expression of uncoupling protein-1 and b 3 -adrenergic receptor in the brown adipose tissue, which is main tissue of diet-induced thermogenesis (30).…”
Section: Discussionmentioning
confidence: 99%
“…We have suggested that D-psicose is partly absorbable in the digestive tract (16) and a 5% D-psicose supplement is enough to suppress hepatic lipogenic enzyme activity and reduce intra-abdominal fat accumulation compared to D-glucose or D-fructose in rats (17,18). If dietary D-psicose influences serum adipocytokines, Dpsicose may be a new functional monosaccharide with anti-diabetic action.…”
mentioning
confidence: 99%
“…However, the reason for the results caused by feeding BRF are is not yet clear, except for the fiber content. Such food ingredients as resistant oligosaccharide, 26) D-psicose, 27) and polyphenols 28) have caused the protection of shortchain fatty acids and hypertrophy in the cecum. The prebiotic effects by BRF including or excluding fiber need to be investigated.…”
Section: Discussionmentioning
confidence: 99%